FINANCIAL AND NON-FINANCIAL FACTORS AFFECTING SUKUK IJARAH RATINGS - Maulidina, Rizky Awaliyah; Bustami, Abiyajid; Maulana, Indra (MSJ : Majority Science Journal, 2024)
This study aims to analyse what affects the rating of sukuk ijarah as seen from financial and non-financial factors. This research is quantitative research using the SPSS application. the sample of this research is companies that issue sukuk ijarah in the 2014-2018 period and are rated by PEFINDO. Indicators of financial factor variables are measured by CR (Current Ratio), ROA (Return on Asset), TATO (Total Asset Turn Over) and DER (Debt to Equity Ratio). While the non-financial factors used are the age of sukuk. The results of this research are financial ratios that affect sukuk ratings are CR and ROA. Where seen from the partial test these two ratios are significant. Meanwhile, if examined simultaneously CR, ROA, TATO, DER and sukuk age on sukuk ratings, the results have a significant effect. This means that all financial ratios and sukuk age simultaneously affect the ijarah sukuk rating.